PENDIDIKAN SEKS: APAKAH PERLU DISAMPAJKAN KEPADA REMAJA? - Hari Arnirullah Rahrnan Hari Arnirullah Rahrnan; Eddy Purnomo Eddy Purnomo (LPMPP Universitas Negeri Yogyakarta, 1999)
Who actually has the duty of delivering sex educationto adolescents? It is not easy to decide who should give sexeducation and how it should be given, because many stilldo not know what sex education really is and how it is implemented.All this time many have assumed that sex is always relatedto coition, reproduction, health, and morals. Some thinkthat sex is something